The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1089/jmf.2005.8.343
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Protective Effect of D-003, a Mixture of High-Molecular-Weight Primary Acids from Sugar Cane Wax, on Liver Damage Induced by Galactosamine in Rats

Abstract: D-003 is a mixture of very-high-molecular-weight aliphatic primary acids purified from sugar cane wax, wherein octacosanoic acid is the most abundant. Experimental and clinical studies have shown that D-003 lowers cholesterol and prevents plasma lipoprotein peroxidation (LP). D-003 has protected against the histological changes characteristic of CCl4- and paracetamol-induced hepatic injury in rats, in which LP plays a pivotal role for explaining the resulting hepatotoxicity. Galactosamine induces hepatotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…It has been shown that when octacosanol (60 mg/kg BW) is orally administered to rats, not only octacosanol but also octacosanoic acid, an oxidation product of octacosanol, appears in the liver and the hepatic amount of octacosanoic acid is a few times higher than that of octacosanol [ 35 ]. Noa et al [ 36 ] reported that oral administration of D-003, a mixture of high molecular weight primary acids, such as octacosanoic acid, purified from sugar cane wax, protected against CCl 4 -induced acute liver injury in rats. In addition, it is known that LDL prepared from rats administered with D-003 is less susceptible to in vitro lipid peroxidation induced by copper ion and a free radical generator, 2,2'-azobis(2-amidinopropane), than LDL from rats without D-003 administration [ 37 ], like the case of administered policosanol [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that when octacosanol (60 mg/kg BW) is orally administered to rats, not only octacosanol but also octacosanoic acid, an oxidation product of octacosanol, appears in the liver and the hepatic amount of octacosanoic acid is a few times higher than that of octacosanol [ 35 ]. Noa et al [ 36 ] reported that oral administration of D-003, a mixture of high molecular weight primary acids, such as octacosanoic acid, purified from sugar cane wax, protected against CCl 4 -induced acute liver injury in rats. In addition, it is known that LDL prepared from rats administered with D-003 is less susceptible to in vitro lipid peroxidation induced by copper ion and a free radical generator, 2,2'-azobis(2-amidinopropane), than LDL from rats without D-003 administration [ 37 ], like the case of administered policosanol [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the last years, sugarcane has raised interest regarding its nutraceutic properties. Several studies have shown beneficial effects of sugarcane extracts on models in vivo in the stimulation of the immune response, protection against liver damage, intestinal function recovery, protection against some infections, antitrombotic and antistress effects or growth stimulation (Koge et al ., ; Noa et al ., ; El‐Abasy et al ., , ; Amer et al ., ; Lo et al ., ; Motobu et al ., ; Yamauchi et al ., ). On searching the origin of these beneficial effects, it has been found that sugarcane has a powerful antioxidant activity (Abbas et al ., ; Feng et al ., ), and it is known that oxidative damage is involved in many human diseases such as cancer, cardiovascular diseases or other degenerative disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators [2,3] have consistently proved on in vivo models the antioxidant properties of high molecular weight alcohols contained in the wax. Sugar cane also contains phenolic acids, flavonoids and other phenolic compounds [4,5], which could account for certain antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%